Acalabrutinib: A Selective Bruton Tyrosine Kinase Inhibitor for the Treatment of B-Cell Malignancies - Abbas, Hussein A.; Wierda, William G. (Frontiers in Oncology, 2021)
Bruton tyrosine kinase (BTK) is a validated target for treatment of B-cell malignancies, and oral inhibitors of BTK have emerged as a standard of care for these diseases. Acalabrutinib is a second generation, highly selective, potent, covalent BTK inhibitor that exhibits minimal off-target activity in in vitro assays, providing the potential to improve tolerability over the first-in-class BTK inhibitor, ibrutinib. Acalabrutinib was approved for the treatment of relapsed/refractory mantle cell lymphoma (MCL) and chronic lymphocytic leukemia (CLL) in the US in 2017 and 2019, respectively. Acalabrutinib is also undergoing trials for other B-cell malignancies, both as monotherapy and in combinations. In this review, we discuss results from clinical trials evaluating the efficacy and safety of acalabrutinib in patients with CLL, MCL, and Waldenstrom’s macroglobulinemia. Recent phase 3 data showed that acalabrutinib improved progression-free survival (PFS) compared with rituximab plus idelalisib or rituximab plus bendamustine in patients with relapsed/refractory CLL, and acalabrutinib with or without obinutuzumab improved PFS compared with chlorambucil plus obinutuzumab in patients with treatment-naïve CLL. Overall, acalabrutinib had a tolerable safety profile, with most adverse events being grade 1/2 severity (most commonly headache and diarrhea) and a low rate of discontinuation due to adverse events.